2003
DOI: 10.2307/1543232
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and Processes of Larval Emergence in an Estuarine Parasite System

Abstract: Trematode parasites in intertidal estuaries experience constantly varying conditions, with the presence or absence of water potentially limiting larval transport between hosts. Given the short life spans (< or =24 h) of cercariae, emergence timing should be optimized to enhance the probability of successful transmission. In the present study, field measurements and laboratory experiments identified processes that regulate the emergence of cercariae from their first intermediate snail hosts in an intertidal mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
49
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 44 publications
3
49
0
2
Order By: Relevance
“…The estimated transmission pressure was highly seasonal, in accordance with expectations based on available knowledge of temperature effects (e.g. , Fingerut et al 2003, Al-Kandari et al 2007, Studer et al 2010, and complemented the results found in the present study, clearly supporting the inferences made. Given the short lifespan of cercariae (< 24 h), the timing of emergence is crucial and should be optimised to enhance the probability of successful transmission to the next host.…”
Section: Temperaturesupporting
confidence: 93%
See 2 more Smart Citations
“…The estimated transmission pressure was highly seasonal, in accordance with expectations based on available knowledge of temperature effects (e.g. , Fingerut et al 2003, Al-Kandari et al 2007, Studer et al 2010, and complemented the results found in the present study, clearly supporting the inferences made. Given the short lifespan of cercariae (< 24 h), the timing of emergence is crucial and should be optimised to enhance the probability of successful transmission to the next host.…”
Section: Temperaturesupporting
confidence: 93%
“…The surprisingly high infection intensities in amphipods (well above 100 parasites per amphipod of the same early developmental stage) confirmed that 'bursts' of cercarial emergence occur (Fredensborg et al 2004b, Keeney et al 2007). Some of these heavily-infected amphipods were captured because sampling took place during optimal conditions for transmission, which presumably occurs during low tides when water temperatures in tide pools increase, exceeding the minimum temperature for cercarial production and emergence from snails , Fingerut et al 2003, Al-Kan-89 Mar Ecol Prog Ser 455: 79-93, 2012 dari et al 2007, Studer et al 2010. Amphipods infected with a certain number of metacercariae beyond a lethal threshold are, however, unlikely to survive for long (Fredensborg et al 2004b, Bates et al 2010.…”
Section: Second Intermediate Amphipod Hostsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because their snail hosts were large and abundant, these cercariae comprised a substantial component of parasite productivity. Cercariae are released from snails in a daily pulse 16 and have ephemeral life spans of about 24 h. The annual cercarial biomass produced by all C. californica trematodes could therefore be compared with the standing crop biomass of other (long-lived) animals. Annual production of cercariae was about threefold that of trematode parthenitae standingstock biomass and threefold to tenfold that of winter bird biomass (Fig.…”
mentioning
confidence: 99%
“…Temperature, in addition to light and water conditions, is one of the main drivers of cercarial emergence through, either directly or indirectly, an acceleration of both the maturation and the liberation of the cercariae. Cercarial emergence from the snail host can be stimulated by a change in temperature, with the eff ect of this infl uence being often trematode-specifi c (Mouritsen, 2002;Fingerut et al, 2003;Ahmed et al, 2006;Poulin, 2006;Koprivnikar & Poulin, 2009a,b;Vignoles et al, 2014). Consequently, in order to initiate ecological studies on a given trematode group, a determination of the optimum temperature must be one of the fi rst steps to be carried out before other parameters can be reasonably investigated.…”
mentioning
confidence: 99%